2017
DOI: 10.18632/oncotarget.19044
|View full text |Cite
|
Sign up to set email alerts
|

miRNA and lncRNA as biomarkers in cholangiocarcinoma(CCA)

Abstract: The microRNAs are a group of 20 nucleotides-long non-coding RNAs. By binding to the 3’UTR region of target mRNA, microRNAs can perform extensive actions mediating gene expression at post-trancriptional stages. It makes microRNAs serve as very crucial regulators in various biological progress including carcinogenesis. Long non-coding RNAs, however, are a subgroup of RNA with the length of 200 nucleotides. Unlike microRNAs, long non-coding RNAs can form secondary of tertiary domain based on their length. With th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 113 publications
2
38
0
Order By: Relevance
“…TMB is correlated with clinical outcome in multiple cancer types treated with CPI (65,66). Previous studies indicated that TMB levels correlated with gene mutations in tumors (25,40,67,68). TMB-H has been reported to correlate with the generation of neoantigens and potential clinical responses to immunotherapies (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMB is correlated with clinical outcome in multiple cancer types treated with CPI (65,66). Previous studies indicated that TMB levels correlated with gene mutations in tumors (25,40,67,68). TMB-H has been reported to correlate with the generation of neoantigens and potential clinical responses to immunotherapies (69).…”
Section: Discussionmentioning
confidence: 99%
“…The alignment of the sequences from tumor tissue samples and matched blood samples were considered to be an effective method for detecting somatic mutations (22)(23)(24). To date, many studies on potential biomarkers for CCA have been reported (25)(26)(27). Ong et al (28) identified and validated 206 somatic mutations in 187 genes, including somatic mutations in 10 newly implicated genes, using Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Nevertheless, none of these has been convincingly validated and the power of single factors in predicting survival is limited. 17,18 Additionally, growing research interest is headed to novel biomarkers with potential predictive and prognostic value such as non-coding RNAs and exosomal proteins, [19][20][21] though this research field is still in its infancy. Hence, there remains an unmet need for a more accurate patients' stratification to inform clinical decision making as well as a rationale trials design.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Aberrant transcriptomic change would occur subsequent to genetic and epigenetic modifications. Previous studies have confirmed the abnormal microRNA profiles in both CCA tumor tissues and cell lines . Mass spectrometry (MS)‐based proteomics has become a useful tool for the analysis of different biofluids to find accurate and specific protein biomarkers for risk stratification, diagnosis, and prognosis .…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have confirmed the abnormal microRNA profiles in both CCA tumor tissues and cell lines. [14][15][16] Mass spectrometry (MS)-based proteomics has become a useful tool for the analysis of different biofluids to find accurate and specific protein biomarkers for risk stratification, diagnosis, and prognosis. 17 Studies focused on proteomics have identified a specific peptide, SSP411 protein, in bile and urine showed better diagnostic value than the general non-specific tumor markers used in serum.…”
Section: Introductionmentioning
confidence: 99%